Scientific Translation for Publication: The Impact of Using Rubber Ropes and Balance Tools on Some Physical Abilities and Offensive Skills of Al-Karkh First Education Team Players Aged (14-16) Years - Najah , Noor; Radhi , Ahmed; Hussain , Fouad (Journal of Physical Education, 2025)
The study aimed to prepare exercises using rubber ropes and balance tools together, and to determine their effect on some of the physical abilities and offensive skills of the Karkh Primary Education players aged 14-16 years in handball. The researchers used the experimental method with two control and experimental groups with a pre-test and a post-test. As for the sample, it was chosen intentionally, namely the players of the first Karkh education team, aged (14-16) years, in handball. They were randomly divided into two groups, control and experimental, with (8) players for each group. The most important physical abilities were identified (strength characterized by speed, explosive power, and endurance of speed), and some offensive skills (dribbling, handling, and shooting). After which the appropriate tests for each variable were chosen and the exploratory experiment was conducted on a sample of the research community, for the purpose of identifying the suitability of the tests and tools used. After conducting the main experiment and extracting the results, appropriate statistical methods were used to treat them statistically. The researchers concluded that the use of rubber ropes and balance tools had a positive effect in developing some physical abilities and offensive skills in handball. The experimental group also achieved better results in the variables studied compared to the control group